Associations of obsessive–compulsive symptoms with clinical and neurocognitive features in schizophrenia according to stage of illness. Issue 1 (30th March 2015) - Kim, Sung-Wan; Jeong, Bo-Ok; Kim, Jae-Min; Shin, Il-Seon; Hwang, Michael Y.; Paul Amminger, G.; Nelson, Barnaby; Berk, Michael; McGorry, Patrick; Yoon, Jin-Sang
Abstract: This study aimed to investigate the association of obsessive–compulsive symptoms with clinical and neurocognitive features in patients with schizophrenia. This study enrolled 163 people with schizophrenia who were receiving risperidone monotherapy. Comorbid obsessive–compulsive symptoms were assessed using the Yale–Brown Obsessive–Compulsive Scale, and subjects with a score≥10 constituted the obsessive–compulsive symptom group ( n =30, 18.4%). The learning index was significantly higher in patients with obsessive–compulsive symptoms than in those without such symptoms after adjusting for age, stage (early and chronic), duration of illness, and CDSS score. However, there was no significant interaction between obsessive–compulsive symptoms and stage of illness. Scores on Positive and Negative Syndrome Scale, Calgary Depression Scale for Schizophrenia, and Beck Depression Inventory were significantly higher in the obsessive–compulsive symptom group. In addition, the Subjective Well-being under Neuroleptic Treatment score was significantly lower in the obsessive–compulsive symptom group. In conclusion, comorbid obsessive–compulsive symptoms in patients with schizophrenia were associated with a higher learning ability without a significant interaction with stage of illness. However, schizophrenia patients with obsessive–compulsive symptoms had more severe psychotic and depressive symptoms and poorer quality of life. Highlights: Patients with obsessive–compulsive symptoms had more severe psychotic symptoms. They had more severe depressive symptoms and poorer quality of life. Comorbid obsessive–compulsive symptoms were associated with higher learning ability.